PENERAPAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 13 PEKANBARU - Tika Ryani; Gustimal Witri; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research started from the problem of low Mathematichs study result by the fourth year students of SDN 13 Pekanbaru is under Standard of Minimum Completeness (KKM) that is 70. From 20 students only 6 (30%) students reach the KKM. The purpose of this research is to improve Mathematics study result of fourth year students of SDN 13 Pekanbaru. This research is a Classroom Action Research (PTK) conducted in two cycles. This research was conducted in fourth year studen of SDN 13 Pekanbaru Academic Year 2018-2019 with 20 students. Based on result of the research and analysis concluded through the application of the approach of Indonesian Realistic Mathematichs Education (PMRI) can improve students mathematichs study result. Increased teacher and students activity in the learning process is due to teacher already accustomed approach Indonesian Realistic Mathematichs Education (PMRI). Students study result have increased from cycle I to cycle II. Student study result before the action that reached the KKM only 6 students (30%) with average 58.25, then in the first cycle increased to 11 (58%) students reached the KKM with average 75 and average increased by 29%, and in second cycle increased to 17 (89%) student reached the KKM with average 84 and average increased by 44%.Key Words: Study Result, Indonesian Realistic Mathematics Education(PMRI), Mathematics